Validity Issues In Accommodating Reading Tests - G. Sireci, Stephen (Penerbit Universiti Sains Malaysia, 2008)
National Assessments seeks to include all students in the sampling frame from which students are selected to participate in the assessment. However, some students with disabilities (SWD) are either unable to take tests under standard testing conditions or are unable to perform at their best under standard testing conditions. In many testing situations, accommodations to standard testing conditions are given to SWD to improve measurement of their knowledge, skills and abilities. This practice is in the pursuit of more valid test score interpretation; however, it produces the ultimate psychometric oxymoron – an accommodated standardized test. In this paper, I review validity issues related to test accommodations and summarize some empirical studies in this area. The focus of the paper is on accommodations for reading tests because some types of accommodations on these tests are particularly controversial. The specific accommodations emphasized in this review are extended time and oral (read-aloud) accommodations. A review of professional standards, validity theory, and recent empirical research in this area suggests that extended time accommodations may be appropriate for reading tests, but read-aloud accommodations are likely to alter the construct measured. Suggestions for determining when to provide accommodations and how to report scores from accommodated test administrations are provided.